Prospective evAluatIon foR inhalation devices in Greek patients with COPD and asthma: The PAIR study. (February 2020) - Karampitsakos, Theodoros; Hillas, Georgios; Zervas, Eleftherios; Bakakos, Petros; Stratakos, Grigorios; Dimakou, Katerina; Manali, Efrosyni; Bouros, Demosthenes; Papiris, Spyridon; Tzouvelekis, Argyrios; ,
Abstract: Introduction: Chronic obstructive pulmonary disease (COPD) and asthma remain a major health burden. Adherence to inhaled therapy is critical in order to optimize treatment effectiveness. Properly designed questionnaires can assess patients' satisfaction with their inhaler devices. Patients and methods: A total of 766 patients with COPD, asthma or Asthma-COPD Overlap (ACO) were initially enrolled. During their first visit, patients were classified into three groups (Diskus™, Elpenhaler®, Turbuhaler®). Patients completed the FSI-10 questionnaire on Day 0 and Day 60. Test-retest reliability was evaluated. Results: A total of 705 patients completed the study. FSI-10 questionnaire had good test-retest reliability (Total Intraclass Correlation Coefficient: 0.86). All dry powder inhaler (DPIs) yielded satisfactory results. Median score of FSI-10 questionnaire in first visit (FSI-10-I) was significantly higher for patients receiving Elpenhaler® (45, 95% CI: 44 to 46) than patients receiving Diskus™ (42, 95% CI: 41 to 43) and Turbuhaler® (42, 95% CI: 41 to 43) (p < 0.001). Accordingly, median score of FSI-10 questionnaire in the final visit (FSI-10-II) was significantly higher for patients receiving Elpenhaler® (46, 95% CI: 45 to 47) than patients receiving Diskus™ (42, 95% CI: 41 to 43) and Turbuhaler® (43, 95% CI: 42 to 44) (p < 0.001). Conclusion: FSI-10 questionnaire had good test-retest reliability and thus can be used in the follow-up of patients with COPD, asthma and ACO. All DPIs were highly acceptable among all study groups. Elpenhaler® achieved significantly higher ratings than Diskus™ and Turbuhaler® in FSI-10 score and presented higher preference among patients with obstructive lung diseases.